2019
DOI: 10.1111/ijd.14617
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous tuberculosis in Rio de Janeiro, Brazil: description of a series of 75 cases

Abstract: Background Brazil is one of the highest tuberculosis (TB) burden countries of the world. Cutaneous tuberculosis (CTB) is a rare form of extrapulmonary manifestation of tuberculosis. This study aimed to describe the clinico‐evolutive, laboratory and therapeutic aspects of CTB cases among patients from a cohort with TB in Rio de Janeiro, Brazil. Methods Cases of diagnosed CTB with microbiologic confirmation or clinical response to anti‐tuberculous treatment associated with positive smear or histopathological fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 68 publications
(145 reference statements)
0
14
2
14
Order By: Relevance
“…1,6 In Europe, the predominant form of cutaneous tuberculosis is lupus vulgaris, which may represent 61.1% of the cases, 7 whereas scrofuloderma is the most common presentation in some developing countries such as Brazil. 5 According to the WHO, Brazil is one of the twenty countries in the ranking with the highest incidence of tuberculosis, 8 and 40% of patients over 45 years of age with typical cutaneous lesions may have coexistent pulmonary tuberculosis, 9 which was not apparently the case of this patient.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…1,6 In Europe, the predominant form of cutaneous tuberculosis is lupus vulgaris, which may represent 61.1% of the cases, 7 whereas scrofuloderma is the most common presentation in some developing countries such as Brazil. 5 According to the WHO, Brazil is one of the twenty countries in the ranking with the highest incidence of tuberculosis, 8 and 40% of patients over 45 years of age with typical cutaneous lesions may have coexistent pulmonary tuberculosis, 9 which was not apparently the case of this patient.…”
Section: Discussionmentioning
confidence: 88%
“…Cutaneous manifestations of tuberculosis are classified into true cutaneous tuberculosis or tuberculids. 5 Cutaneous tuberculosis includes a continuous spectrum according to the degree of immunity and the route of infection. Some authors further define the infection according to the amount of bacilli found in skin lesions as paucibacillary or multibacillary, the latter being associated with more deficient degrees of immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Além disso, no presente estudo foi identificado um predomínio de aproximadamente 66% no sexo masculino, diferentemente do descrito na maioria dos estudos sobre TBC. 33,34,35,36,37,38 Azevedo e Oliveira (2016), por exemplo, analisaram 26 pacientes com diagnóstico de TBC, sendo 18 mulheres e 8 homens (30%). 39 Porém, percebese que na Espanha, Índia, China, Hong Kong e Mali, o sexo masculino apresenta maiores taxas de incidência desta doença.…”
Section: Dados Epidemiológicosunclassified
“…48 A faixa etária em que se encontraram mais casos de TBC foi entre 41-60 anos, com mediana de 53 anos, sendo essa um pouco mais tardia do que o observado na literatura, que evidencia resultados entre 35 e 48 anos. 33,34,36,38,39,41,50 No estudo de Zhang et al (2018) mais de 77,6% dos pacientes analisados com diagnóstico de TBC estavam na faixa etária entre 10 e 49 anos, com a maior incidência (61,9%) entre 10 e 39 anos. 19 No presente estudo, somente 41,6% dos pacientes estavam entre a faixa etária de 10-49 anos.…”
Section: Dados Epidemiológicosunclassified